Evaluation method for curing degree of silicon steel self-adhesive coating

The infrared spectrum of the self-adhesive coating of silicon steel is analyzed by Fourier transform attenuated total reflection infrared spectroscopy, and the reaction conversion rate of the curing degree is calculated, which solves the problem that the degree of curing of silicon steel is not accurately judged in the prior art. , realizes scientific and reliable judgment of solidified state and production control.

CN119290799APending Publication Date: 2025-01-10BAOSHAN IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310835971.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art cannot accurately judge the curing degree of silicon steel self-adhesive coating, which leads to difficulties in production control and performance optimization. The commonly used empirical methods are greatly affected by human factors, which are prone to misjudgment.

Method used

The cured silicon steel sheet was scanned and tested by Fourier transform attenuated total reflection infrared spectroscopy (ATR-IR). By analyzing the reaction characteristic peaks and reference peaks in the infrared spectrum, the reaction conversion rate of the curing degree was calculated and the reaction conversion rate was determined. The degree of curing of the self-adhesive coating of silicon steel.

Benefits of technology

This method avoids the influence of human factors, the test results are scientific and reliable, and are not disturbed by the apparent color of the sample and the thickness of the coating. It can accurately judge the curing state of the self-adhesive coating of silicon steel, and provides a method of machine-by-machine detection or rapid analysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290799A_ABST
    Figure CN119290799A_ABST
Patent Text Reader

Abstract

The invention discloses a method for evaluating the curing degree of a silicon steel self-adhesive coating. The method comprises the following steps: S1, acquiring an infrared spectrogram of the silicon steel self-adhesive coating by using Fourier transform attenuated total reflection infrared spectroscopy; s2, analyzing the infrared spectrogram, identifying and selecting a reaction characteristic peak and a reference peak of the silicon steel self-adhesive coating; s3, performing integral calculation on the reaction characteristic peak and the reference peak selected in the step S2 to obtain the reaction conversion rate of the curing degree of the self-adhesive coating; and S4, judging the curing degree of the silicon steel self-adhesive coating according to the reaction conversion rate of the curing degree of the self-adhesive coating. According to the method, the influence of human factors is avoided, the sample does not need to be specially treated, the test sensitivity and the resolution ratio are relatively good, the test result is relatively scientific and reliable, the method is not interfered by the apparent color of the sample and the thickness of the coating, and the method can be used as a beside-machine detection or rapid analysis method for the curing state of the self-adhesive coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating curing degree detection, and in particular to a method for evaluating the curing degree of a silicon steel self-adhesive coating. Background Art

[0002] Under the action of hot pressing, the silicon steel self-adhesive coating can cause a bonding reaction between adjacent silicon steel sheets in the laminated core, and the laminated core is assembled and formed by surface-to-surface contact and fixing, making the stacking molding process pollution-free, the core fixing strength is high, the magnetic vibration noise is small, the core efficiency is high, etc. It is widely used in wind turbines, automobile drive motors, and micro motors.

[0003] Currently, commercialized silicon steel self-bonding coatings are typically composed of thermosetting epoxy resins and their curing agents. The coatings react chemically during the subsequent baking and curing process to form an insulating layer. According to the state changes of the coating during the baking and curing process, the silicon steel self-bonding coatings are mainly divided into three states: the initial state is when the coating is not heated and basically no obvious curing reaction occurs, and the coating is in the form of wet coating; the intermediate state is when a certain degree of but incomplete curing reaction occurs after heating, and the steel mill delivers the material after a baking and curing process, and the final state is when the coating is heated again to complete the curing reaction, and the coating is in the form of a finished product of C-3 category (ASTM 976 standard) silicon steel insulating coating that no longer has inter-sheet bonding effect.

[0004] The curing degree of the self-adhesive coating directly affects many properties of the coating product, such as adhesion, insulation, corrosion resistance, oil resistance, and chemical resistance. The intermediate curing process window performed by silicon steel manufacturers is narrow, and production control is difficult. Research on its curing degree is of great significance for optimizing process technology, improving product performance and quality assessment. For example, the self-adhesive coating disclosed in Chinese patents CN03150582.1 and CN109013253B is the process practice of silicon steel manufacturers to control the intermediate curing degree.

[0005] Generally, the curing degree of the intermediate coating can be roughly judged by the wipe marks of solvents such as alcohol and acetone, or by testing the peel strength of the coated steel sheet after the intermediate coating is processed by hot pressing to form the final state. These empirical methods are subject to many human factors and cannot accurately judge the curing degree of the coating; and different types of self-adhesive coatings have different corresponding curing properties, which is very likely to cause misjudgment according to the above methods. Summary of the invention

[0006] In view of the defect that the curing degree of the self-bonding coating cannot be accurately judged in the prior art, the purpose of the present invention is to provide a method for evaluating the curing degree of the silicon steel self-bonding coating. The cured silicon steel sheet is scanned and tested by attenuated total reflection infrared spectroscopy (ATR-IR), and the changes in typical groups of the self-bonding coating are obtained to analyze and evaluate the curing state of the coating. The present invention avoids the influence of human factors, does not require special treatment of the sample, has good test sensitivity and resolution, and the test results are relatively scientific and reliable, and are not affected by the apparent color of the sample and the thickness of the coating. It can be used as a method for machine-side detection or rapid analysis of the curing state of the self-bonding coating.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The present invention provides a method for evaluating the curing degree of a silicon steel self-bonding coating, comprising the following steps:

[0009] S1, infrared spectrum of silicon steel self-bonding coating obtained by Fourier transform attenuated total reflection infrared spectroscopy;

[0010] S2, analyzing the infrared spectrum to identify and select the reaction characteristic peaks and reference peaks of the silicon steel self-adhesive coating;

[0011] S3, obtaining the reaction conversion rate of the curing degree of the self-bonding coating according to the reaction characteristic peak selected in step S2 and the reference peak;

[0012] S4, judging the curing degree of the silicon steel self-adhesive coating according to the reaction conversion rate of the curing degree of the self-adhesive coating.

[0013] Preferably, the step S1 specifically includes the following steps:

[0014] S11, sample preparation, select a test area of ​​no less than 2 cm × 2 cm on the silicon steel self-adhesive coating sample to be tested, and clean the surface of the test area;

[0015] S12, test equipment preparation, select a Fourier transform infrared spectrometer with an attenuated total reflection accessory, and use fastening components to press to ensure that the silicon steel self-adhesive coating sample to be tested is bonded to the ATR crystal;

[0016] S13, performing a scanning test on the silicon steel self-bonding coating sample to be tested to obtain an infrared spectrum of the silicon steel self-bonding coating.

[0017] Preferably, in step S11, when cleaning the surface of the test area, a cloth or a cotton ball dipped in a solvent is used for wiping, the number of wiping back and forth is ≤3 times, and the time for the solvent to volatilize on the surface of the sample after wiping is ≤5 seconds; the solvent is pure water or alcohol; and / or

[0018] In step S12, the ATR crystal is made of zinc selenide, diamond or germanium, and the light transmittance range of the ATR crystal is 400-5000cm -1 The refractive index ranges from 2.4 to 4.0; and / or

[0019] In step S13, in the scanning test, the number of scans is set to 16 to 32 times, and the resolution is set to 2 to 6 cm. -1 , the spectrum scanning range is 4000~6000cm -1 , aperture is 6 mm; and / or

[0020] In the step S13, in the scanning test, air is used as the background, and the H2O and CO2 background signals are subtracted.

[0021] Preferably, in step S2:

[0022] The reaction characteristic peak is an absorption peak where chemical bond changes occur in the self-adhesive coating during the curing reaction, and the number of the reaction characteristic peaks is ≥1;

[0023] The reference peak is an absorption peak that does not participate in the curing reaction, and the number of the reference peaks is ≥1.

[0024] Preferably, the reaction characteristic peak is selected from the absorption peaks of cyano, epoxy, carbonyl and amide groups that undergo chemical bond changes during the curing reaction;

[0025] The reference peak is selected from the absorption peaks of benzene ring, hydroxyl group and methyl group which do not participate in the curing reaction.

[0026] Preferably, the reaction characteristic peak is selected at a wave number of 1737 cm -1 、1562cm -1 Nearby absorption peaks;

[0027] The reference peak selected wave number is 1508cm -1 、1606cm -1 The absorption peak near .

[0028] Preferably, in step S3, the calculation formula of the reaction conversion rate C% value of the curing degree of the self-bonding coating is as follows:

[0029] C=100-(A 特征峰 / A 参比峰 ) / (A 特征峰0 / A 参比峰0 )×100

[0030] Wherein, the C% value is the reaction conversion rate of the curing degree of the self-bonding coating;

[0031] A 特征峰is the peak area of ​​the reaction characteristic peak of the self-adhesive coating after curing;

[0032] A 参比峰 is the peak area of ​​the reference peak of the cured self-adhesive coating;

[0033] A 特征峰0 is the peak area of ​​the reaction characteristic peak of the uncured self-bonding coating;

[0034] A 参比峰0 is the peak area of ​​the reference peak of the uncured self-bonding coating.

[0035] Preferably, in step S4, the judgment basis for characterizing the curing degree of the silicon steel self-bonding coating is as follows:

[0036] When the reaction conversion rate of the curing degree of the self-adhesive coating is less than 30%, the self-adhesive coating is under-cured and the glue overflow phenomenon is serious;

[0037] When the reaction conversion rate of the curing degree of the self-adhesive coating is between 30% and 70%, the self-adhesive coating is an ideal intermediate coating;

[0038] When the reaction conversion rate of the curing degree of the self-adhesive coating is greater than 70%, the self-adhesive coating is over-cured and the bonding performance is deteriorated.

[0039] Preferably, when the reaction conversion rate of the curing degree of the self-bonding coating is between 40% and 60%, the self-bonding coating is an ideal intermediate coating.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The method for evaluating the curing degree of the silicon steel self-bonding coating of the present invention uses Fourier transform attenuated total reflection infrared spectroscopy (ATR-IR) to scan and test the cured silicon steel sheet, obtain the absorption peak wavelength data of the reactive group in the coating curing process, and analyze and summarize the absorption peaks in the spectrum. After data processing, the reaction conversion rate of the curing degree of the self-bonding coating is obtained, so as to judge the curing degree of the silicon steel self-bonding coating; this method does not require complex pre-treatment of the sample, the test result is relatively scientific and reliable, and is not affected by factors such as sample color and film thickness, and the test process does not cause damage to the sample;

[0042] 2. The method for evaluating the curing degree of the silicon steel self-bonding coating of the present invention uses attenuated total reflection infrared spectroscopy (ATR-IR) to monitor the changes in typical groups of the self-bonding coating to analyze and evaluate the curing state of the coating, avoiding the influence of human factors, and does not require special treatment of the sample. The test sensitivity and resolution are good, and the test results are relatively scientific and reliable. It is not affected by the apparent color of the sample and the thickness of the coating. It can be used as a method for machine-side detection or rapid analysis of the curing state of the self-bonding coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0044] Figure 1 is the ATR-IR spectra of samples No. 1-9 used in the embodiments of the present invention;

[0045] Figure 2 is the ATR-IR spectra of the coatings obtained by samples No. 1, 3, 4, and 5 in the embodiment of the present invention after different baking times;

[0046] Figure 3 Schematic diagram of the effect of the intermediate curing process on the curing conversion rate of the coating;

[0047] Figure 4 It is a relationship diagram between the main properties (bonding strength and glue overflow degree) of the self-bonding coating in the present invention and the curing conversion rate. DETAILED DESCRIPTION

[0048] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.

[0049] The present invention provides a method for evaluating the curing degree of a silicon steel self-bonding coating. The method is based on Fourier transform attenuated total reflection infrared spectroscopy, and the reflection signal of a silicon steel sample with a self-bonding coating is collected to obtain an infrared spectrum of the coating. The reaction characteristic peaks participating in the curing reaction and the reference peaks not participating in the curing reaction in the infrared spectrum are identified, and integral operations and data processing are performed on them to obtain a reaction conversion rate of the curing degree of the self-bonding coating that is strongly correlated with the curing degree of the self-bonding coating, thereby judging the curing degree of the silicon steel self-bonding coating.

[0050] The method for evaluating the curing degree of a silicon steel self-bonding coating of the present invention comprises the steps of test preparation, peak separation and selection, data processing, and judging the curing degree, and specifically comprises the following steps:

[0051] S1, infrared spectrum of silicon steel self-bonding coating obtained by Fourier transform attenuated total reflection infrared spectroscopy;

[0052] This process is the test preparation stage, including sample preparation, test equipment preparation and parameter adjustment, specifically including the following processes:

[0053] S11, sample preparation, select a test area of ​​no less than 2 cm × 2 cm on the silicon steel self-adhesive coating sample to be tested, and clean the surface of the test area;

[0054] Specifically, a test area of ​​not less than 2cm×2cm is selected on the silicon steel self-adhesive coating sample to be tested. The surface of the area is flat and free of obvious oil and dust. When cleaning the surface of the test area, it can be wiped with a cloth dipped in solvent or a cotton ball, but the number of wiping back and forth is ≤3 times, and the residual solvent on the surface of the sample after wiping is ≤5 seconds. A hot hair dryer can be used as an aid if necessary; the solvents are limited to pure water and alcohol.

[0055] Since there are a considerable number of active reaction groups inside the intermediate self-adhesive coating, the above-mentioned strict restriction measures must be taken when cleaning the surface of the sample to prevent solvents such as water and alcohol from damaging the coating structure and affecting the test results.

[0056] S12, test equipment preparation, select a Fourier transform infrared spectrometer with an attenuated total reflection accessory, and use fastening components to press to ensure that the silicon steel self-adhesive coating sample to be tested is bonded to the ATR crystal;

[0057] Specifically, a Fourier transform infrared spectrometer (IR) with an attenuated total reflection accessory (ATR) is selected, and the test area of ​​the sample is ensured to fully cover the crystal surface of the ATR accessory, and the fastener is used to press (pressure of about 70N) to ensure the fit between the test sample and the ATR crystal. Among them, the ATR crystal material is preferably zinc selenide, diamond or germanium, and its light transmittance range should be 400-5000cm -1 The light refractive index ranges from 2.4 to 4.0.

[0058] S13, performing a scanning test on the silicon steel self-bonding coating sample to be tested to obtain an infrared spectrum of the silicon steel self-bonding coating.

[0059] Specifically, the core of this process is to adjust the parameters. In the ATR-IR test method, after the instrument is turned on and self-checked and calibrated, the number of scans is set to 16 to 32 times and the resolution is 2 to 6 cm. -1 , the spectrum scanning range is 4000~600cm-1, the aperture is 6mm; when scanning the sample to be tested, take air as the background, subtract the H2O and CO2 background signals, and make appropriate corrections to the spectrum baseline (among which, the correction is made by the software that comes with the ATR-IR test equipment. When operating, click "Subtract H2O", "Subtract CO2" and other backgrounds in sequence, and the software will automatically fine-tune the spectrum, which is regarded as correction).

[0060] S2, analyzing the infrared spectrum to identify and select the reaction characteristic peaks and reference peaks of the silicon steel self-adhesive coating;

[0061] The core of this process is peak separation and selection. When analyzing the infrared spectrum obtained from the above scanning test, the main absorption peaks of the self-adhesive coating during the curing process are compared and identified, and then the absorption peaks that undergo chemical bond changes are selected as reaction characteristic peaks ≥1, and the absorption peaks that do not participate in the curing reaction are selected as reference peaks ≥1. Among them, the reference peak can be selected from the absorption peaks of groups such as benzene ring (C6H6), hydroxyl (-OH), and methyl (-CH3) that do not participate in the curing reaction; the reaction characteristic peak can be selected from the absorption peaks of groups such as cyano (-CN), epoxy (-CH(O)CH-), carbonyl (C=O), and amide (-CONH2) that undergo chemical bond changes during the curing reaction.

[0062] Since the molecular vibration of each chemical functional group in the coating selectively absorbs electromagnetic radiation in the infrared light region, a peak that does not undergo chemical reaction and whose spectrum position remains unchanged is selected in the infrared spectrum as a reference object, and then the reaction characteristic peaks of the reactive groups that undergo chemical bond changes are identified, and their changes are identified to analyze the curing state of the coating. This is the principle of the method of the present invention.

[0063] Since the current commercial silicon steel self-bonding coatings are basically based on thermosetting epoxy resin and its curing agent as the main ingredients in the formula, several typical self-bonding coatings and ATR-IR spectra of different curing states were tested according to the above method principle. The reference peak wave number that does not participate in the curing reaction can be selected at 1508cm -1 、1606cm -1 The characteristic peak wave number of the curing reaction was selected at 1737 cm -1 、1562cm -1 Nearby. The wave number is 1562cm -1 Nearby is the absorption peak of amide group (-CONH2). As the degree of curing reaction increases, the absorption peak intensity gradually decreases. At the same time, when the curing reaction proceeds, the wave number 1737cm -1 It is a new peak and gradually strengthens, which is suitable as a characteristic peak of the reaction.

[0064] S3, integrating and calculating the reaction characteristic peak and the reference peak selected in step S2 to obtain the reaction conversion rate of the curing degree of the self-adhesive coating;

[0065] Specifically, for all the reaction characteristic peaks and reference peaks selected above, the peak area A is calculated by integrating them respectively. 特征峰 and A 参比峰 .

[0066] The C% value is defined as the reaction conversion rate of the curing degree of the self-bonding coating, and the calculation formula is:

[0067] C=100-(A 特征峰 / A参比峰 ) / (A 特征峰0 / A 参比峰0 )×100.

[0068] Wherein, C% is the reaction conversion rate of the curing degree of the self-adhesive coating; A 特征峰 A is the peak area of ​​the reaction characteristic peak of the self-adhesive coating after curing; 参比峰 A is the peak area of ​​the reference peak of the self-adhesive coating after curing; 特征峰0 A is the peak area of ​​the reaction characteristic peak of the uncured self-adhesive coating (paint); 参比峰0 is the peak area of ​​the reference peak of the uncured self-bonding coating (paint).

[0069] S4, judging the curing degree of the silicon steel self-adhesive coating according to the reaction conversion rate of the curing degree of the self-adhesive coating.

[0070] This step is the stage of judging the degree of curing, and the degree of curing of the silicon steel self-adhesive coating can be judged according to the reaction conversion rate of the degree of curing of the self-adhesive coating calculated above.

[0071] For the intermediate state of epoxy silicon steel self-bonding coating, the specific basis for judging its curing degree is:

[0072] After analysis and summary, it is believed that the reaction conversion rate C% value can reflect the degree of curing of the self-adhesive coating: when the reaction conversion rate C% value is less than 30%, the self-adhesive coating is under-cured, the coating hardness is low, the glue overflow phenomenon is serious, and the bonding strength is not high at this time; when the reaction conversion rate C% value is between 30 and 70% (preferably 40 to 60%), the self-adhesive coating has the highest bonding strength, the glue overflow situation can also be controlled, and an ideal intermediate coating is obtained; when the reaction conversion rate C% value is greater than 70%, the self-adhesive coating is over-cured, and although no glue overflow can be achieved, the bonding performance is significantly deteriorated.

[0073] That is, the reaction conversion rate of the intermediate state suitable curing degree of the epoxy silicon steel self-bonding coating is 30-70%, preferably 40-60%. The self-bonding coating within this range is an ideal intermediate state coating, and the bonding strength and the degree of glue overflow control can achieve a good balance. If the reaction conversion rate of the curing degree of the self-bonding coating is too low (i.e., lower than 30%), the coating is under-cured and the glue overflow phenomenon is serious; if the reaction conversion rate of the curing degree of the self-bonding coating is too high (i.e., higher than 70%), the coating is over-cured and the coating bonding performance is deteriorated.

[0074] The following is a further introduction to a method for evaluating the curing degree of a silicon steel self-adhesive coating with reference to specific examples.

[0075] Example

[0076] Table 1 lists the background conditions of all embodiments and comparative examples of the present invention (the sample substrate brand is B50A800);

[0077] Table 1 Background information of samples No. 1-9

[0078]

[0079]

[0080] All embodiments and comparative examples were tested by infrared spectroscopy using the following steps:

[0081] Get a 3 cm long and 4 cm wide self-adhesive coated silicon steel sheet, dip a small amount of anhydrous ethanol with cotton cloth, and quickly wipe the coating surface under a hair dryer for later use; the visible solvent residence time on the coating surface is 1 to 2 seconds.

[0082] The sample to be tested was mounted on the diamond crystal surface of the ATR accessory, and after applying a pressure of about 70N to fix it, the Nicolet 6700 infrared spectrometer was turned on. After the instrument self-check and calibration, the scanning number was set to 32 times and the resolution was 4cm. -1 , aperture 6mm, spectral scanning range 4000~600cm -1 , the sample to be tested can be scanned and tested, H2O and CO2 background can be subtracted, and the baseline of the spectrum can be appropriately corrected.

[0083] Depend on Figure 1 Analysis shows that: wave number 1606cm -1 and 1508cm -1 The absorption peak at is the characteristic absorption peak of the benzene ring group. It has a sharp peak shape and is not affected by any conditions such as coating thickness and baking curing. It always exists and its relative intensity remains basically unchanged. It can be used as an obvious reference peak that does not participate in the curing reaction.

[0084] Wave number 1562cm -1 The absorption peak of the amide group is at 1737cm. As the curing degree progresses, its peak intensity becomes lower and lower, and the peak area becomes smaller and smaller. It is a consumable group in the curing reaction of the self-adhesive coating. -1 The absorption peak of the amide carbonyl group is at , and its peak intensity gradually increases and the peak area becomes larger and larger as the degree of curing proceeds. It belongs to the generative group in the curing reaction of the self-adhesive coating; the absorption peaks of these groups can be used as obvious reaction characteristic peaks.

[0085] Similarly, at wave number 914 cm -1 There is an epoxy group absorption peak at the region, which will also participate in the curing reaction, and the epoxy group will undergo ring-opening addition; wave number 2190~2160cm -1There is a cyano group absorption peak at , which changes from a double peak to a single peak as the curing reaction proceeds. The absorption peaks of these two groups will also gradually weaken as the curing reaction proceeds.

[0086] However, 914cm -1 The absorption intensity of the epoxy group absorption peak is relatively low, at 2190-2160 cm -1 The cyanide absorption peak at is calculated by integrating the two peaks together to find the area. As the curing reaction proceeds, the double peak gradually transforms into a single peak, which will cause certain inaccuracies in subsequent calculations and judgments on the curing state of the coating. Therefore, these two peaks are used as comparative proportions for subsequent analysis.

[0087] The peak areas of the six peaks mentioned above were obtained by integrating them separately, and the peak areas were calculated by C = 100 - (A 特征峰 / A 参比峰 ) / (A 特征峰0 / A 参比峰0 )×100 to calculate the reaction conversion rate C% value of the curing degree of the self-adhesive coating. Table 2 lists the -1 and 1737cm -1 The characteristic peak of the reaction at 2190 cm -1 and 914cm -1 The peak areas of the characteristic peak and reference peak of the comparative example and the corresponding calculated results are shown in FIG.

[0088] Table 2 Curing conversion rate of self-adhesive silicon steel coating of samples No. 1-9

[0089]

[0090] From Table 2, it can be seen that whether it is the reaction consumption peak such as 1562cm -1 , or the reaction generates peaks such as 1737cm -1 When it is the reaction characteristic peak, with the increase of the degree of curing, the reaction conversion rate C% value of the self-bonding coating increases accordingly. Combined with the main coating properties shown in Table 1, it is clear that the C% value can quantitatively reflect the curing state of the coating product.

[0091] From the baking process conditions of samples 1, 3, 4, and 5, it can be seen that under the conditions of consistent film thickness and baking temperature, the longer the baking time, the better the degree of curing should be. Combined with the C% value data calculated based on the characteristic peak area in Table 2, and Figure 2 From the changes in the characteristic peaks, it can be seen that the conversion rate of the coating gradually increases from 0% in the wet state to 30% for sample 5, about 40% for sample 3, and then to about 70% for sample 4, which is consistent with the actual performance trend of the relevant properties of the coating samples.

[0092] However, if 914cm -1 and 2190cm -1 It is a characteristic peak. Compared with sample No. 3, the baking time of sample No. 4 is longer, but its reaction conversion rate is reduced, which is inconsistent with the actual performance trend of the relevant properties of the coating sample. Therefore, it is not suitable to be selected as a suitable characteristic peak to participate in the calculation of the conversion rate, and to judge the degree of curing of the intermediate state of the coating. Therefore, it is used as a comparative example in the present invention for illustration.

[0093] According to the data in Tables 1 and 2, the sample curing process and related performance tests were extended and done. Figure 3 It can be seen that the reaction speed of the epoxy self-bonding coating is faster when the reaction conversion rate is below 70%. This is also the time when the silicon steel production plant obtains self-bonding coated silicon steel with a suitable intermediate state curing degree. The faster reaction process also confirms that the steel plant's curing process window is relatively narrow; and when the coating reaction conversion rate is above 70%, the reaction speed is relatively slow, so the core plant's process window for final state curing is relatively flexible and controllable.

[0094] Figure 4 It reflects that the reaction conversion rate for obtaining the appropriate curing degree of the intermediate state of the epoxy silicon steel self-bonding coating is 30-70%, preferably 40-60%. The bonding strength and overflow control degree of the self-bonding coating within this range can achieve a good balance. If the reaction conversion rate value is too low (i.e., lower than 30%), the coating will be under-cured and the overflow phenomenon will be serious; if the conversion rate value is too high (i.e., higher than 70%), the coating will be over-cured and the coating bonding performance will deteriorate.

[0095] In summary, the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for evaluating the curing degree of a silicon steel self-adhesive coating, characterized in that: The following steps are involved: S1, infrared spectrum of silicon steel self-bonding coating obtained by Fourier transform attenuated total reflection infrared spectroscopy; S2, analyzing the infrared spectrum to identify and select the reaction characteristic peaks and reference peaks of the silicon steel self-adhesive coating; S3, integrating and calculating the reaction characteristic peak and the reference peak selected in step S2 to obtain the reaction conversion rate of the curing degree of the self-adhesive coating; S4, judging the curing degree of the silicon steel self-adhesive coating according to the reaction conversion rate of the curing degree of the self-adhesive coating.

2. The method for evaluating the curing degree of silicon steel self-bonding coating according to claim 1, characterized in that: The step S1 specifically includes the following steps: S11, sample preparation, select a test area of ​​no less than 2 cm × 2 cm on the silicon steel self-adhesive coating sample to be tested, and clean the surface of the test area; S12, test equipment preparation, select a Fourier transform infrared spectrometer with an attenuated total reflection accessory, and use fastening components to press to ensure that the silicon steel self-adhesive coating sample to be tested is bonded to the ATR crystal; S13, performing a scanning test on the silicon steel self-bonding coating sample to be tested to obtain an infrared spectrum of the silicon steel self-bonding coating.

3. The method for evaluating the curing degree of silicon steel self-bonding coating according to claim 2, characterized in that: In the step S11, when cleaning the surface of the test area, a cloth or a cotton ball dipped in a solvent is used for wiping, the number of wiping back and forth is ≤3 times, and the time for the solvent to volatilize on the surface of the sample after wiping is ≤5 seconds; the solvent is pure water or alcohol; and / or In step S12, the ATR crystal is made of zinc selenide, diamond or germanium, and the light transmittance range of the ATR crystal is 400-5000cm -1 The refractive index ranges from 2.4 to 4.0; and / or In step S13, in the scanning test, the number of scans is set to 16 to 32 times, and the resolution is set to 2 to 6 cm. -1 , the spectrum scanning range is 4000~6000cm -1 , aperture is 6 mm; and / or In the step S13, in the scanning test, air is used as the background, and the H2O and CO2 background signals are subtracted.

4. The method for evaluating the curing degree of silicon steel self-adhesive coating according to claim 1, characterized in that: In step S2: The reaction characteristic peak is an absorption peak where chemical bond changes occur in the self-adhesive coating during the curing reaction, and the number of the reaction characteristic peaks is ≥1; The reference peak is an absorption peak that does not participate in the curing reaction, and the number of the reference peaks is ≥1.

5. The method for evaluating the curing degree of the silicon steel self-adhesive coating according to claim 4, characterized in that: The reaction characteristic peak is selected from the absorption peaks of cyano, epoxy, carbonyl and amide groups that undergo chemical bond changes during the curing reaction; The reference peak is selected from the absorption peaks of benzene ring, hydroxyl group and methyl group which do not participate in the curing reaction.

6. The method for evaluating the curing degree of the silicon steel self-adhesive coating according to claim 4, characterized in that: The reaction characteristic peak selected wave number is 1737cm -1 、1562cm -1 Nearby absorption peaks; The reference peak selected wave number is at 1508cm -1 、1606cm -1 absorption peak near .

7. The method for evaluating the curing degree of silicon steel self-bonding coating according to claim 1, characterized in that: In step S3, the calculation formula of the reaction conversion rate C% value of the curing degree of the self-bonding coating is as follows: C=100-(A 特征峰 / A 参比峰 ) / (A 特征峰0 / A 参比峰0 )×100 Wherein, the C% value is the reaction conversion rate of the curing degree of the self-bonding coating; A 特征峰 is the peak area of ​​the reaction characteristic peak of the self-adhesive coating after curing; A 参比峰 is the peak area of ​​the reference peak of the cured self-adhesive coating; A 特征峰0 is the peak area of ​​the reaction characteristic peak of the uncured self-bonding coating; A 参比峰0 is the peak area of ​​the reference peak of the uncured self-bonding coating.

8. The method for evaluating the curing degree of silicon steel self-adhesive coating according to claim 1, characterized in that: In step S4, the curing degree of the silicon steel self-bonding coating is determined based on the following: When the reaction conversion rate of the curing degree of the self-adhesive coating is less than 30%, the self-adhesive coating is under-cured and the glue overflow phenomenon is serious; When the reaction conversion rate of the curing degree of the self-adhesive coating is between 30% and 70%, the self-adhesive coating is an ideal intermediate coating; When the reaction conversion rate of the curing degree of the self-adhesive coating is greater than 70%, the self-adhesive coating is over-cured and the bonding performance is deteriorated.

9. The method for evaluating the curing degree of silicon steel self-bonding coating according to claim 8, characterized in that: When the reaction conversion rate of the curing degree of the self-adhesive coating is between 40% and 60%, the self-adhesive coating is an ideal intermediate coating.

Citation Information

Patent Citations

  • Production method of self-adhesive coating for electrical steel

    CN109013253B

  • Production method of electrical steel plate for magnetic suspension long stator

    CN1279190C